Focusing on the Merseburg process: benefits on industrial decarbonization and waste minimization. Issue 1 (31st December 2022) - Avşar, Cemre; Tümük, Didem; Yüzbaşıoğlu, Abdullah Emre; Gezerman, Ahmet Ozan
ABSTRACT: Greenhouse gas emissions, mostly CO2 release, on anthropogenic sources and industrial applications have triggered an increase in global temperature, termed as global warming and as-related climate change. Phosphogypsum (PG) is a by-product of wet process phosphoric acid production, mainly composed of calcium sulfate dihydrate (gypsum) together with some impurities. The annual accumulation rate of PG has reached 300 Mtons, and there is a need for an efficient, continuous, and bulk consumption strategy. Industrial by-products have been used as an alternative raw material for CO2 capture as a solid carbonate compound. PG is rich in calcium, being a promising candidate for CO2 mineral sequestration. In this manner, the Merseburg process (the ammono-carbonation of gypsum) allows both CO2 capture and PG recycling. Products are ammonium sulfate, a well-desired nitrogenous fertilizer and CaCO3, a functional filler material utilized in various kinds of industries. The Merseburg process allows dual environmental benefits by allowing the consumption of an industrial by-product and performing CO2 capture technology, both contributing to sustainable development goals. This study gives a brief summary of the environmental possible impacts of the Merseburg process in terms of CO2 sequestration and phosphogypsum management. GRAPHICAL ABSTRACT: UF0001